Alberto Baltra and the teaching of Political Economy in law studies in Chile - Marmolejo González, Crispulo Mario (Revista Pedagogía Universitaria y Didáctica del Derecho, 2022)
This article reviews the general aspects of Professor Alberto Baltra's contribution to the teaching of political economy in Law studies in Chile. The teaching of economic issues in chilean legal studies arose in the first half of the 19th century and continues to this day. Political economy is the antecedent of current courses in Economic Law taught in several law schools throughout the country. Alberto Baltra's academic activity was demanding, innovative and anticipated some of the challenges imposed by the current context of legal education in Chile. The work studies some aspects of Professor Baltra´s teaching based on texts and testimonies from some of his disciples and students.